Effect of Autologous Serum Therapy (AST) as Adjuvant Management in Morphea: A Pilot Study - Nopriyati; Hasbiallah Yusuf; Ahmad Ligar Suherman (Jurnal RSMH Palembang, 2024)
Morphea, or localized scleroderma, is a chronic autoimmune disease characterized by sclerosis of the skin, subcutaneous tissue, and bones. Morphea therapy targets the inflammatory component, cytokine release and collagen activation and deposition. The mechanism of action of autologous serum therapy (AST) is based on the principle of induction of desensitization or tolerance to pro-inflammatory signals. The patient's clinical improvement criteria were calculated using the localized scleroderma cutaneous assessment tool (LoSCAT) based on physical examination. This study used a one group pre-test – post-test experimental design on morphea patients at the Dermatology, Venereology, and Aesthetics (DVE) Polyclinic, Allergy and Immunology Subdivision in Dr. Mohammad Hoesin General Hosptial (RSMH) Palembang in May-October 2023. This study included 7 morphea patients who met the inclusion criteria for AST injection in 8 weeks duration. The Dermatology Life Quality Index (DLQI) assessment carried out before the AST and after the 8th AST showed that all patients experienced improvements in quality of life after 8 weeks. There was a decrease in LoSCAT scores in 5 patients (71.4%), while there was no change in LoSCAT scores in 2 patients (28.6%). Side effects of pain at the AST injection site in 3 patients (42.8%) were tolerable without painkillers, while other patients did not experience any side effects. The paired T-test statistical test on patients before AST and after AST treatment for 8 weeks showed that there was a significant difference in the mean DLQI and LoSCAT with p-value respectively 0.003 and 0.032. There is a significant difference in the mean DLQI and LoSCAT in study patients before AST and after AST for 8 weeks. There were side effects in the form of local pain at the AST injection area in 3 patients which were well tolerated without painkillers.